The art of controversy : political cartoons and their enduring power - Navasky, Victor S. (A Borzoi book, 2013)
"A lavishly illustrated, witty, and learned look at the awesome power of the political cartoon throughout history to enrage, provoke, and amuse. As a former editor of The New York Times Magazine and the longtime editor of The Nation, Victor Navasky knows just how incendiary--and transformative--cartoons can be. Here Navasky guides readers through some of the greatest cartoons ever sketched--by George Grosz, David Levine, Herblock, Honore Daumier, Thomas Nast, Ralph Steadman, et al.--as he asks what makes cartoons so uniquely positioned to affect our minds and our hearts. Incorporating neuroscience, psychology, and a sweeping historical view of the cartoon's evolution, The Art of Controversy is a book for all lovers of satire, politics, and the vastly underappreciated and endlessly surprising art form of the political cartoon. "--